VISIT THE TOMB OF KI MAROGAN: PRESERVATION OF RELIGIOUS TRADITION IN MUSLIM MALAY COMMUNITY - Trisiah, Anita; Puspita, Weni; Septiyanti, Reni (Journal of Malay Islamic Studies, 2019)
The custom of some Palembang Malay Muslim communities to visit the tomb of Ki Marogan is a religious tradition that has lasted for years. This study wants to see what are the motives behind the Palembang Muslim community to maintain this tradition and how their perceptions of these pilgrimage habits. By using the method of observation and in-depth interviews found the fact that there are various motives behind the pilgrimage tradition to the Ki Merogan tomb, ranging from forms of respect for the figure of Ki Merogan Ulama, known as a charismatic figure of Ulama and its important role in the development of Islam in the city of Palembang, to with the motive of smelling khurafat in the form of a desire to pay a vow because their request was granted after praying at the grave of Ki Marogan. Meanwhile pilgrims consider that the tradition of pilgrimage to the grave of Ki Merogan is a good habit and does not violate Islamic teachings. Some even believe that the pilgrimage to the tomb of Ki Merogan is a must because it is a form of respect for the great ulemas of Palembang who have high karomah.